Learning Environment, Achievement Motivation and Career Decision Making among Gifted Secondary School Students - Joel, Ogutu Peter (American Journal of Education and Learning, 2019)
The study investigated the relationship between learning environment, achievement motivation and career decision making of gifted students. A total of 130 gifted students selected from six secondary schools participated in the study. Mean, standard deviation, Independent sample t-test, Spearman rank order correlation Co-efficient and multiple regression analysis were used to analyse the data. The result of the hypotheses of the study showed a significant relationship between the learning environment and achievement motivation (r = .72, p < 0.01). T-test for independent samples revealed that the differences between real and ideal classroom learning environment were statistically significant (p < 0.05) for the entire classroom learning environment indicators. The study also revealed a significant correlation between the classroom learning environment and career decision making among gifted secondary school students. The study established the role of the learning environment and achievement motivation on career decision making and made recommendations to stakeholders in education to assist students to realize their potential in achievement motivation and career decision making. The study concluded that gifted students’ motivation was linked to the classroom learning environment. The support given in school and families were of major importance to their motivation to achieve. In addition, the students’ motivation was anchored on the kind of classroom learning environment. Like ideal environment was found to be positively correlated to achievement motivation and career decision making. However, challenges in the classroom learning environment were counterproductive to achievement motivation and career decision making.